PERSEPSI KONSUMEN TERHADAP BAURAN RITEL TRADISIONAL DAN RITEL MODERN DI KOTA JEMBER - Mohammad Dimyati (RELASI : JURNAL EKONOMI, 2015)
The purpose of this study is to investigate consumer perceptions of the retail mix of traditional and modern retail in Jember city and to determine the presence or absence of significant differences in consumer perceptions of the retail mix of traditional and modern retail. The sampling technique in this study using purposive sampling. Methods of data collection is done by distributing questionnaires to 100 questionnaires to the respondents coming from the four districts selected the District of Jember City, District of Kaliwates, Sumbersari, Patrang, and Pakusari. The analysis tools are different descriptive analysis and Wilcoxon test. This research found that there are differences in consumer perceptions of the 6 variables retail mix of traditional retail and modern retail in Jember City. To 6 variables include variable pricing, promotions, location, service, convenience shopping and premium products. Also note also that there are no differences in consumer perceptions of the distance variable in the traditional retail and modern retail in Jember City. Distinguishing variables that are most closely/related to the perception of consumers is the convenience of shopping variables. So the convenience of shopping to be a major consideration that differentiates consumer perceptions of the retail mix of traditional and modern retail.